Effect of Excipients on the Phenolic Content in Pumpkin Leaf Extracts after Their Introduction into Semisolid Pharmaceutical Forms and Evaluation of In Vitro Stability - Al Nachar, khuloud; Hasian, Jameela; Agha, Isam Hasan (Jordan Journal of Pharmaceutical Sciences, 2025)
The present study aimed to formulate semi-solid pharmaceutical forms from pumpkin leaves (Cucurbita pepo Casper). Total phenolic content was measured after extracting the leaves from Ghouta, Syria. Plant extracts were prepared from Cucurbita pepo Casper leaves using four solvents: ethanol (70%), ethanol, aqueous, and methanol extract. The phenolic content of each extract was quantified. The most effective extracts were incorporated into semi-solid pharmaceutical forms. The influence of excipients on phenolic content was evaluated by measuring phenolic levels in the semisolid formulations and analyzing changes in viscosity and consistency on the shelf. The aqueous extract of Cucurbita pepo 'Casper' leaves exhibited the highest phenolic content, with a concentration of 2.21 ± 11.77 mg/g dry powder. This extract was selected for formulation into three distinct pharmaceutical bases. Among the formulations, the water-in-oil (w/o) cream demonstrated the highest phenolic content and superior stability compared to the oil-in-water (o/w) cream. Stability tests conducted over a three-month period confirmed that the w/o cream maintained optimal stability. Thus, the w/o cream was determined to be the most effective formulation.